Influence of Different Simulation Models for Electrical Characteristic Analysis of the Arrester of AC Filter - Xuemin HUANG; Junwen DENG; Jing DENG; Xin LUO; Yongxia HAN (Zhongguo dianli)
AC filter is an important equipment in DC transmission system. This paper mainly analyzes the influence of simulation model on the electrical characteristics (overvoltage, current and absorbed energy) of the arresters for AC filter, and carries out the modeling and simulation calculation for the filter input and AC filter bus grounding fault based on PSCAD electromagnetic simulation program. The simulation result shows that when the AC filter is put into operation and the traditional large group model for a single filter (model 1) was used for simulation, the arresters of the working filters did not act, which is different from the actual situation; under the filter input and filter bus grounding fault, the overvoltage of the arrester of each group of filters in complete parameter model (model 3) was lowered by 21% compared to that in the original system model (model 2) and model 1, and the current was reduced by up to 53%, but the absorbed energy increased by up to 56%. Therefore, if the complete parameter model is not used in the insulation design, the voltage and current design value of the arrester could be too large while the energy design value could be too small. At the same time, the action of the arresters of other AC filters in the same group could be easily ignored when the filter is put into operation.